Konsekuensi Penggunakan Entity Theory sebagai Konsep Dasar Standar Akuntansi Perbankan Syari’ah - Iwan Triyuwono (Jurnal Akuntansi dan Auditing Indonesia)
The objective of the paper essentially is to criticize an important assumption of PSAK No. 59, that is, entity theory which is implicitly utilized as a basis for setting PSAK No. 59. After analyzing the theory, it is indicated that entity theory is strongly influenced by capi¬talistic and utilitarian values which consequently: (1) shapes accounting to be (1) egoistic, (2) ma¬terialistic, (3) masculine, (4) quantitative, and (5) neglects externalities. Under the values of capitalism and utilitarianism, it is probable that users of the Financial Statements of Islamic Banks will behave in the same manner with the conventional ones.